2018
DOI: 10.1158/1055-9965.epi-17-0627
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Breast Cancer Survival by Molecular Subtypes in the United States

Abstract: Using Surveillance, Epidemiology and End Results cancer registry data, we assessed survival after breast cancer diagnosis among women diagnosed during 2010 to 2013 and followed through December 31, 2014. Breast cancer molecular subtypes defined by joint hormone receptor [HR, estrogen receptor (ER) and/or progesterone receptor (PR)] and HER2 status were assessed. Multiple imputation was used to fill in missing receptor status. Four-year breast cancer-specific survival per molecular subtypes and clinical/demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
285
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(331 citation statements)
references
References 31 publications
(52 reference statements)
13
285
1
3
Order By: Relevance
“…Our observation of decreased HER2 + rMBC incidence in the most recent time period is consistent with reported results of improved long-term outcomes after neoadjuvant/adjuvant treatment with HER2-targeted therapy [26]. Improvements in early disease treatment targeted at hormone receptor and HER2-positive disease have reduced overall distant relapse rates but resulted in a new profile of rMBC disease that may be more aggressive with a higher chemoresistant probability [27, 28]. …”
Section: Discussionsupporting
confidence: 89%
“…Our observation of decreased HER2 + rMBC incidence in the most recent time period is consistent with reported results of improved long-term outcomes after neoadjuvant/adjuvant treatment with HER2-targeted therapy [26]. Improvements in early disease treatment targeted at hormone receptor and HER2-positive disease have reduced overall distant relapse rates but resulted in a new profile of rMBC disease that may be more aggressive with a higher chemoresistant probability [27, 28]. …”
Section: Discussionsupporting
confidence: 89%
“…The primary limitation of the current study is incompleteness of birthplace information. Although multiple-imputation methods have been used previously to correct for missing ER, PR, and HER2 status, 45 we did not impute these because this method has not been fully expanded to the nationwide cancer registry data, and important predictors (eg, survival time) for missing HER2 status were not available in our data. In cancer registry data, birthplace is abstracted by tumor registrars from existing medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Triple‐negative breast cancers have a poorer prognosis compared with other subtypes, in part because this subtype is more likely to be diagnosed at an advanced stage, and the development of targeted therapies has lagged behind . Notably, a recent US population‐based study found that 4‐year relative survival was ≥95% for patients diagnosed with stage I disease across all breast cancer subtypes …”
Section: Selected Findingsmentioning
confidence: 99%
“…State Variation in Female Breast Cancer Incidence and Mortality Rates and Rate Ratios in White and Black Women and Mammography Screening Prevalence DECEMBER 2019found that 4-year relative survival was ≥95% for patients diagnosed with stage I disease across all breast cancer subtypes 63. Geographic Variations in Incidence, Mortality, and Mammography…”
mentioning
confidence: 99%